FACTORS ASSOCIATED WITH INTRACYTOPLASMIC SPERM INJECTION OUTCOME IN MEN WITH AZOOSPERMIA AND SEVERE OLIGOZOOSPERMIA - putra, donny eka; Utomo, Trisula (Indonesian Journal of Urology, 2016)
Objective: This study is assigned to evaluate factors that associated with intracytoplasmic sperm injection (ICSI) outcome. Material & methods: A retrospective study design is used to evaluate couples who seeking help for infertility problems at Permata Hati Infertility Clinic, Sardjito General Hospital Yogyakarta. The outcome measures were fertilization and clinical pregnancies rates. All analyses were performed with SPSS statistical software, version 20.0. Result: Forty-five couples participated in this study with mean age 33.69 ± 5.38 years for men and 30.53 ± 4.79 years for women. Of 56 ICSI cycles, there were 43 successful fertilizations (95.6%) and 14 clinical pregnancies (31.1%). In multivariate analysis, factors associated with successful clinical pregnancies were women’s age (p = 0.034, 95% CI 0.005-0.8), number of ICSI cycle (p = 0.045, 95% CI 0.001-0.93), and sperm morphology (p = 0.019, 95% CI 1.648- 253). In bivariate analysis, only men’s age is significantly associated with successful fertilization (p = 0.006, 95% CI 7.22-16.43). Conclusion: Factors associated with outcome of ICSI are women’s age, number of ICSI cycle, and sperm morphology.